Targeted Chemotherapy of Glioblastoma Spheroids with an Iontronic Pump. Issue 5 (12th April 2021) - Waldherr, Linda; Seitanidou, Maria; Jakešová, Marie; Handl, Verena; Honeder, Sophie; Nowakowska, Marta; Tomin, Tamara; Karami Rad, Meysam; Schmidt, Tony; Distl, Joachim; Birner‐Gruenberger, Ruth; von Campe, Gord; et al.
Abstract: Successful treatment of glioblastoma multiforme (GBM), the most lethal tumor of the brain, is presently hampered by (i) the limits of safe surgical resection and (ii) "shielding" of residual tumor cells from promising chemotherapeutic drugs such as Gemcitabine (Gem) by the blood brain barrier (BBB). Here, the vastly greater GBM cell‐killing potency of Gem compared to the gold standard temozolomide is confirmed, moreover, it shows neuronal cells to be at least 10 4 ‐fold less sensitive to Gem than GBM cells. The study also demonstrates the potential of an electronically‐driven organic ion pump ("GemIP") to achieve controlled, targeted Gem delivery to GBM cells. Thus, GemIP‐mediated Gem delivery is confirmed to be temporally and electrically controllable with pmol min −1 precision and electric addressing is linked to the efficient killing of GBM cell monolayers. Most strikingly, GemIP‐mediated GEM delivery leads to the overt disintegration of targeted GBM tumor spheroids. Electrically‐driven chemotherapy, here exemplified, has the potential to radically improve the efficacy of GBM adjuvant chemotherapy by enabling exquisitely‐targeted and controllable delivery of drugs irrespective of whether these can cross the BBB. Abstract : An electronically‐driven ion pump is engineered for the targeted delivery of the charged chemotherapeutic gemcitabine to brain cancer cells. Delivery of drug ions over a cation exchange membrane at currents in the nanoampere range triggers brain cancer cell death and microtumor disintegration. Local gemcitabine treatment offers a therapeutical window, in contrast to standard treatment.